Knowledge Management Model in Improving the Performance of PT Kl Jakarta - Risalina Risalina; Masydzulhak Djamil Mz; Ahmad Badawi Saluy (Publikasi Indonesia, 2022)
This study aims to analyze the function of the Knowledge Management Model in improving performance and to obtain the most appropriate model in improving performance at PT KL. The population used in this study is the Knowledge Management division of PT KL Group. A questionnaire consists of written questions made based on indicators of research variables that respondents must respond to. The data analysis technique used in this research is AHP (Analytical Hierarchy Process) developed by Thomas L. Saaty. Testing the model using the latest version of ANP Super Decision Software 3.2.0, to analyze the function of the Knowledge Management Model in improving the performance of PT KL with two criterias. The first criteria (criteria-1): Quality, Quantity, Timeliness, Cost Effectiveness, Need Supervision, Intrapersonal Effect. The second criterion (criteria-2): Completeness, Connectedness, and Congruence, Perspective & Purpose. The alternatives that can be used to improve the performance of PT KL are: Passive Public Knowledge, Active Public Knowledge, Passive Share Knowledge, Active Share Knowledge, Passive Personal Knowledge, and Active Personal Knowledge. The results obtained indicate that the answers from the respondents have met the consistency requirements and the model has been proven both in terms of sensitivity or stability. The Knowledge Management Model in this study shows the importance of Passive Public Knowledge to improve performance at PT KL